A HFCF-UF method to directly analyze the total concentration of protein-binding drugs. Issue 18 (21st September 2015) - Du, Chaohui; Zhang, Jinfeng; Wang, Xinyu; Ran, Congcong; Li, Qinglian; Jiang, Ye
<x xml:space="preserve">Abstract</x> In the present study, a direct injection hollow fiber centrifugal ultrafiltration (HFCF-UF) method was developed for monitoring liposoluble therapeutic drugs.